Dynamic Phenology of Canopy-Forming Macroalgal Forests within a Tropical Seascape - Shaun K. Wilson; Christopher J. Fulton; Martial Depczynski; Ben Radford; Thomas H. Holmes; Matthew Birt; Cal Faubel; Marjetta L. Puotinen; Mae Noble; Richard D. Evans; Molly Moustaka; Paul Tinkler; et al. (Ecosystems, 2026)
Biomass dynamics of primary producers provide a basis for assessing their capacity to capture carbon and mitigate excess greenhouse gases. Here, we estimate inter-annual and seasonal biomass cycles in canopy-forming Sargassaceae at 19 sites spanning ~ 200 km of the Ningaloo World Heritage Area over 11 consecutive years. Our global average summer estimate of 1.53 kg wet wt m −2 equates to 4.1–9.4 Gg of standing macroalgal carbon (14.9–34.6 Gg CO 2 ) across 38,300 ha of all macroalgae habitats. Biomass estimates did not differ significantly among years but varied by an order of magnitude among sites. Accumulation typically occurred during the spring, followed by a loss of 42–94 Gg wet weight, or 1.4–3.3 Gg organic carbon (5.3–12.0 Gg CO 2 ) fixed in macroalgal habitats during autumn. Seasonal patterns of biomass accumulation and release were, however, spatially and temporally variable, some sites accumulating biomass in autumn and releasing it during the following spring. Spring biomass accumulation was reduced by herbivorous urchins, whilst the extent of macroalgae biomass change in the autumn was directly correlated with sea temperature and standing biomass the previous summer. These findings imply canopy-forming macroalgae provide a regular injection of biomass into the surrounding ecosystems, which support productivity of surrounding habitats and is a potential source of organic carbon for burial in carbon sinks throughout the year. Modelling that seeks to link macroalgae sources with sinks therefore requires a spatially explicit understanding of when seasonal senescence of canopy-forming macroalgae occurs, inter-site variability and the environmental conditions that govern this phenology.

Drivers of benthic invertebrate diversity in the protected Walpole-Nornalup Estuary, southwest Australia - Inês Leal; Michael J. Rule; Paul S. Lavery; Shaun K. Wilson (Biodiversity and Conservation, 2025)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Too hot to handle: Unprecedented seagrass death driven by marine heatwave in a World Heritage Area - Simone Strydom; Kathy Murray; Shaun Wilson; Bart Huntley; Michael Rule; Michael Heithaus; Cindy Bessey; Gary A. Kendrick; Derek Burkholder; Matthew W. Fraser; Katherine Zdunic (Global Change Biology, 2020)
The increased occurrence of extreme climate events, such as marine heatwaves (MHWs), has resulted in substantial ecological impacts worldwide. To date, metrics of thermal stress within marine systems have focussed on coral communities, and less is known about measuring stress relevant to other primary producers, such as seagrasses. An extreme MHW occurred across the Western Australian coastline in the austral summer of 2010–2011, exposing marine communities to summer seawater temperatures 2–5°C warmer than average. Using a combination of satellite imagery and in situ assessments, we provide detailed maps of seagrass coverage across the entire Shark Bay World Heritage Area (ca. 13,000 km 2 ) before (2002 and 2010) and after the MHW (2014 and 2016). Our temporal analysis of these maps documents the single largest loss in dense seagrass extent globally (1,310 km 2 ) following an acute disturbance. Total change in seagrass extent was spatially heterogeneous, with the most extensive declines occurring in the Western Gulf, Wooramel Bank and Faure Sill. Spatial variation in seagrass loss was best explained by a model that included an interaction between two heat stress metrics, the most substantial loss occurring when degree heating weeks (DHWm) was ≥10 and the number of days exposed to extreme sea surface temperature during the MHW (DaysOver) was ≥94. Ground truthing at 622 points indicated that change in seagrass cover was predominantly due to loss of Amphibolis antarctica rather than Posidonia australis , the other prominent seagrass at Shark Bay. As seawater temperatures continue to rise and the incidence of MHWs increase globally, this work will provide a basis for identifying areas of meadow degradation, or stability and recovery, and potential areas of resilience.

A review of global instruments to combat invasive alien species in forestry - Michael Ormsby; Evan Brenton-Rule (Biological Invasions, 2017)

Reproductive synchrony in a habitat-forming kelp and its relationship with environmental conditions - Margaret B. Mohring; Thomas Wernberg; Gary A. Kendrick; Michael J. Rule (Marine Biology, 2013)

The H-mshi antigen is conserved among standard BALB/cBy, C57BL/6J, and wild-derived CAST/Ei and SPRET/Ei inbred strains of mice - Audrey L. Hildebrandt; Angelene M. Cantwell; Michael C. Rule; T. R. King (Immunogenetics, 1999)

Mouse male sterility and histoincompatibility ( mshi ) maps between the D10Mit51/168/212 cluster and D10Mit213 - Michael C. Rule; Raye J. Mutcherson II; Andrew D. Foss; Tien K.-X. Nguyen; Kenute A. Myrie; Thomas R. King (Mammalian Genome, 1999)